2010
DOI: 10.1186/1471-230x-10-39
|View full text |Cite
|
Sign up to set email alerts
|

Role of myosin light chain kinase in intestinal epithelial barrier defects in a rat model of bowel obstruction

Abstract: BackgroundBowel obstruction is a common cause of abdominal emergency, since the patients are at increased risk of septicemia resulting in high mortality rate. While the compartmentalized changes in enteric microfloral population and augmentation of bacterial translocation (BT) have already been reported using experimental obstruction models, alterations in epithelial permeability of the obstructed guts has not been studied in detail. Myosin light chain kinase (MLCK) is actively involved in the contraction of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 46 publications
1
19
0
1
Order By: Relevance
“…The bacterial colony-forming units (CFUs) were calculated and normalized per gram of tissue (CFU/g). 43,44 Ussing Chamber Studies and Macromolecular Flux Assay Muscle-stripped intestinal tissues were opened along the mesenteric border and mounted in Ussing chambers (WPI Instruments, USA). The opening of the chamber (2 cm 2 ) exposed the tissue to 10 ml of circulating oxygenated Krebs buffer.…”
Section: Analysis Of Bacterial Counts In Intestines and Extraintestinmentioning
confidence: 99%
“…The bacterial colony-forming units (CFUs) were calculated and normalized per gram of tissue (CFU/g). 43,44 Ussing Chamber Studies and Macromolecular Flux Assay Muscle-stripped intestinal tissues were opened along the mesenteric border and mounted in Ussing chambers (WPI Instruments, USA). The opening of the chamber (2 cm 2 ) exposed the tissue to 10 ml of circulating oxygenated Krebs buffer.…”
Section: Analysis Of Bacterial Counts In Intestines and Extraintestinmentioning
confidence: 99%
“…Сокращение актино-миозиновых филаментов, которое открывает межклеточные пространства, связано с фос-форилированием легкой цепи (ЛЦ) миозина посредством особого фермента -миозин-ЛЦ-киназы [37]. Помимо физического открытия плотных связей, миозин-ЛЦ-киназа также обеспечивает эндоцитоз белков плотных контактов в вакуольные апикальные пространства.…”
Section: функции кишечного эпителиального барьераunclassified
“…Bacterial endocytosis by epithelial cells was observed after 6 h of obstruction, whereas TJ damage was seen only after 24 h. 15,29,57 The TJ damage in gut tissues after 24 h of obstruction was evidenced by occludin cleavage, ZO-1 destruction, and increased tissue conductance and macromolecular permeability. 15,29,57 Interestingly, continuous epithelial lining on villus surface with no sign of cell death was found at both time points, ruling out loss of cell viability as a cause of bacterial transcellular passage. Normal crypt/villus ratio was observed after 6 h in comparison to villus blunting without crypt hyperplasia after 24 h, suggesting cell sloughing on villus tip may partly contribute to TJ damage at the later time point.…”
Section: Terminal Web Contraction and Brush Border Fanningmentioning
confidence: 99%
“…21,22,26 We and others demonstrated that bacterial endocytosis by epithelial cells preceded TJ damage under inflammatory stress in a doseand time-dependent manner. 15,29,38,57 Therefore, we suspect that bacterial entry through intermicrovillous lipid rafts may trigger activation of intracellular NLRs by the sensing of endosomally derived bacterial structural components (unrelated to virulence factors). The NLRmediated immune responses may adversely cause aggravated inflammatory and oxidative stress, leading to secondary TJ damage in epithelial cells (Fig.…”
Section: Intracellular Immune Signalsmentioning
confidence: 99%
See 1 more Smart Citation